Insights into kinetics, thermodynamics, and mechanisms of chemically activated sunflower stem biochar for removal of phenol and bisphenol-A from wastewater - Lakshmi Prasanna Lingamdinne; Ganesh Kumar Reddy Angaru; Chandrika Ashwinikumar Pal; Janardhan Reddy Koduru; Rama Rao Karri; Nabisab Mujawar Mubarak; Yoon-Young Chang (Scientific Reports, 2024)
Abstract This study synthesized a highly efficient KOH-treated sunflower stem activated carbon (KOH-SSAC) using a two-step pyrolysis process and chemical activation using KOH. The resulting material exhibited exceptional properties, such as a high specific surface area (452 m2/g) and excellent adsorption capacities for phenol (333.03 mg/g) and bisphenol A (BPA) (365.81 mg/g). The adsorption process was spontaneous and exothermic, benefiting from the synergistic effects of hydrogen bonding, electrostatic attraction, and stacking interactions. Comparative analysis also showed that KOH-SSAC performed approximately twice as well as sunflower stem biochar (SSB), indicating its potential for water treatment and pollutant removal applications. The study suggests the exploration of optimization strategies to further enhance the efficiency of KOH-SSAC in large-scale scenarios. These findings contribute to the development of improved materials for efficient water treatment and pollution control.